2013
DOI: 10.1128/jvi.00626-13
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of CHOP/GADD153 during Coronavirus Infectious Bronchitis Virus Infection Modulates Apoptosis by Restricting Activation of the Extracellular Signal-Regulated Kinase Pathway

Abstract: Induction of the unfolded protein response (UPR) is an adaptive cellular response to endoplasmic reticulum (ER) stress that allows a cell to reestablish ER homeostasis. However, under severe and persistent ER stress, prolonged UPR may activate unique pathways that lead to cell death. In this study, we investigated the activation of the protein kinase R-like ER kinase (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
122
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 113 publications
(133 citation statements)
references
References 66 publications
9
122
0
Order By: Relevance
“…Consistent with these findings, activation of luciferase reporters under the control of BiP or GRP94 promoters has been observed in cells infected with SARS-CoV (Chan et al, 2006). ER stress has also been observed in cells infected with other coronaviruses such as MHV (Versteeg et al, 2007) or IBV (Liao et al, 2013). Therefore, ER stress induction is likely a common outcome in cells infected with coronaviruses .…”
Section: Induction Of Er Stress By Coronavirus Infectionsupporting
confidence: 68%
See 2 more Smart Citations
“…Consistent with these findings, activation of luciferase reporters under the control of BiP or GRP94 promoters has been observed in cells infected with SARS-CoV (Chan et al, 2006). ER stress has also been observed in cells infected with other coronaviruses such as MHV (Versteeg et al, 2007) or IBV (Liao et al, 2013). Therefore, ER stress induction is likely a common outcome in cells infected with coronaviruses .…”
Section: Induction Of Er Stress By Coronavirus Infectionsupporting
confidence: 68%
“…The effective inhibition of PKR (and likely also PERK) phosphorylation has been attributed to the nsp2 protein, which dosage dependently restore the PKR-mediated translation suppression of a reporter construct (Wang et al, 2009). The kinetic of eIF2␣ phosphorylation is similar to that of PKR and PERK, which peaks at early infection but drastically reduces afterwards (Liao et al, 2013;Wang et al, 2009). As a result, de novo synthesis of host proteins is not significantly suppressed in IBV-infected cells throughout the course of infection (Wang et al, 2009).…”
Section: Activation Of Isr During Coronavirus Infectionmentioning
confidence: 85%
See 1 more Smart Citation
“…Minakshi et al analyzed this by transfecting Huh7 cells with p3a and luciferase-tagged ER stress-related molecules, showing that it can enhance protein folding, but not activate Endoplasmic Reticulum Associated Degradation (ERAD) Minakshi et al, 2009. The long-term triggering of the PERK pathway can also induce virus-related apoptosis through the expression of its downstream mediators of ATF4 and CHOP, similar to IBV infection (Liao et al, 2013). Padhan et al have shown that protein 3a can lead to increased activation of the p38 MAP kinase pathway and induce the mitochondria to leak cytochrome c to induce apoptosis (Padhan et al, 2008).…”
Section: Sars-cov P3amentioning
confidence: 99%
“…Moreover, GADD153 and c-myc are known to be involved in apoptosis progression. GADD153 is a member of the CCAAT/ enhancer-binding protein family of transcription factors and its expression is markedly enhanced by various cellular stresses (22,23). On the other hand, c-myc is a proto-oncogene and is implicated in various processes including cell growth, proliferation and cell death (24).…”
Section: Discussionmentioning
confidence: 99%